2008
DOI: 10.1152/ajpregu.00808.2007
|View full text |Cite
|
Sign up to set email alerts
|

Weight regain after sustained weight reduction is accompanied by suppressed oxidation of dietary fat and adipocyte hyperplasia

Abstract: A dual-tracer approach (dietary 14C-palmitate and intraperitoneal 3H-H2O) was used to assess the trafficking of dietary fat and net retention of carbon in triglyceride depots during the first 24 h of weight regain. Obesity-prone male Wistar rats were allowed to mature under obesogenic conditions for 16 wk. One group was switched to ad libitum feeding of a low-fat diet for 10 wk (Obese group). The remaining rats were switched to an energy-restricted, low-fat diet for 10 wk that reduced body weight by 14% and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
133
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(150 citation statements)
references
References 60 publications
15
133
2
Order By: Relevance
“…49 In streptozotocin-induced diabetic rats, high-fat diets with a high P/S ratio of 1.0 significantly improved glucose oxidation and incorporation into lipids in adipocyte tissue compared with low P/S ratio diets of 0.3. 10 Moreover, reducing body fat accumulation by lowering dietary fat amount was reported by Jackman et al 50 , who found that obese rats switched to ad libitum feedings of a low-fat diet resulted in a high, steady rate of fat oxidation compared with those switched to an energy-restricted and low-fat diet.…”
Section: Discussionmentioning
confidence: 91%
“…49 In streptozotocin-induced diabetic rats, high-fat diets with a high P/S ratio of 1.0 significantly improved glucose oxidation and incorporation into lipids in adipocyte tissue compared with low P/S ratio diets of 0.3. 10 Moreover, reducing body fat accumulation by lowering dietary fat amount was reported by Jackman et al 50 , who found that obese rats switched to ad libitum feedings of a low-fat diet resulted in a high, steady rate of fat oxidation compared with those switched to an energy-restricted and low-fat diet.…”
Section: Discussionmentioning
confidence: 91%
“…To assess dietary fatty acid oxidation, tissue retention and trafficking of dietary fat, and de novo lipogenesis, an in vivo, 24-h, dual-tracer study was performed as described previously (15,38). On day 2 of the 3-day HFD, animals received an intraperitoneal injection of 3 H2O (200 l, 1 mCi/ml) 1 h prior to the start of the dark cycle, which allows for tracer equilibration with total body water, and measurement of incorporation of tritium in extracted lipid serves as an estimate of net retention of carbon via de novo lipogenesis.…”
Section: Methodsmentioning
confidence: 99%
“…The reductions in leptin and insulin (21,(23)(24)(25), in combination with a number of other neural, nutrient, and endocrine signals, convey an "energy deficit" signal to energy balance control centers within the brain. The result is an increased drive to eat (8,15,21,23,25) and a suppressed energy expenditure (9, 14, 25-27, 33, 35, 44). To maintain the reduced weight, food intake must be proactively limited to the level that expenditure is suppressed.…”
mentioning
confidence: 99%
“…Peripherally, the increase in insulin sensitivity and reversal of metabolic inflexibility primes tissues to utilize and store the impending caloric excess in an energetically efficient manner, in part because the ability to regulate fat oxidation is restored (2,15,38,41). Additionally, studies in both humans and animals suggest that weight loss can lead to an increase in the number of adipocytes, which could facilitate the repletion and expansion of adipose tissue depots (15,24,25). Taken together, these observations provide evidence that the metabolic adaptations to weight reduction not only make it very difficult to sustain the necessary level of calorie restriction, but they also facilitate rapid, efficient weight regain when the inevitable bout of overfeeding occurs.…”
mentioning
confidence: 99%